On bounding credit event risk premia - Jennie Bai; Pierre Collin-Dufresne; Robert S. Goldstein; Jean Helwege (Federal Reserve Bank of New York, 2012)
Reduced-form models of default that attribute a large fraction of credit spreads to compensation for credit event risk typically preclude the most plausible economic justification for such risk to be priced - namely, a contagious response of the market portfolio during the credit event. When this channel is introduced within a general equilibrium framework for an economy comprised of a large number of firms, credit event risk premia have an upper bound of just a few basis points and are dwarfed by the contagion premium. We provide empirical evidence supporting the view that credit event risk premia are minuscule.
Keywords: G12; G10; 330